SEMIOTICS OF VISUAL SYSTEMS IN THE MURALS OF PALESTINE - NOUASRIA Ratiba (Ziglôbitha)
Abstract: This study explores how murals, a powerful form of youth expression and resistance, convey meaning. They use semioticsto analyze how visualelements and iconic level work with any text included linguistic and non-linguistic message to deliver messages about the Palestinian issue and audience desires. Through examining murals through a semioticlens, this research contributes to understanding social identity, The findings show that mural soffer a rich platform for visual communication of cultural struggles. The study encourages further research on murals as a form of art withdeep social and political significance.